Orientation Services and Course Satisfaction among Technical Vocational Education and Training (TVET) Trainees in Kenya - Maren Awuor Omondi; Pamela Raburu; Peter Aloka (Journal of General Education and Humanities, 2022)
The study examined the relationship between orientation guidance services and course satisfaction among trainees in TVET institutions in Kakamega County, Kenya. Holland’s theory of vocational choice guided the study. A concurrent Triangulation design was adopted. The study targeted 12807 trainees, four registrars, 4 Deputy Principals in charge of academics, and 4 Guidance and Counseling Coordinators from the TVET institutions in Kakamega County. The use of questionnaires and interview schedule collected data. The instruments were piloted among 38 trainees from Kisiwa TTI in neighboring Bungoma County of Kenya. The study established a significant positive correlation between orientation services (r=.473; p=.000) and course satisfaction among TVET trainees. Orientation services accounted for 22.1% of the variation in the level of course satisfaction. Based on the findings, it was recommended that the Administrators of TVET institutions ensure the implementation of TVET academic policy in the institutions to enhance the adequate provision of academic services.